Penguatan Kompetensi Guru SDN 01 Kemuning Dalam Pelatihan Pembuatan Bahan Ajar Digital Dengan Aplikasi Kvisoft di Masa Pasca Pandemi - Nila Prihartanti; Nuha Is’af Rosyidah; Rafika Usi Puspita Kusuma Sari; Yasmine Norma Anggraeni; Budhi Setiawan (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
The transition of the learning process in schools due to the Covid-19 pandemic has changed the order of the learning process. Learning that is carried out online is again carried out offline. This has several obstacles faced by teachers and students, one of which is the use of teaching materials in the learning process. Digital teaching materials are one of the things that teachers should continue to develop in facing learning challenges in the post-pandemic period. This training activity on making digital teaching materials with the Kvisoft application is a solution to these challenges. Service activities are carried out in several stages, namely observation, training, and evaluation. The research was conducted using a qualitative research method with a field research approach. The research approach was carried out with a case study approach on the object of research of teachers at SDN 01 Kemuning. From the results of the research, it was found that teachers at SDN 01 Kemuning had not mastered technology in making digital teaching materials. Then, after going through the training stages, significant results were obtained in increasing teacher competence in making digital teaching materials through the Kvisoft application